On Contested Shores The Evolving Role of Amphibious Operations in the History of Warfare - Heck, Timothy; Friedman, B. A. (Marine Corps University Press (MCUP), 2020)
Perhaps no prediction has been as consistently made-and as consistently wrong-as the imminent death of amphibious operations. Whatever the changes in warfare and technology, the necessity of amphibious force projection endures, long outliving those who claim its time has passed. Changes in how amphibious operations are conducted, however, are just as consistent. This essential contributed volume arrives at a vital point of transition. These essays highlight both changes and continuities, examining historical amphibious operations as early as the sixteenth century to the near future, describing both lesser-known cases and offering more nuanced views of famous campaigns, such as Gallipoli and Normandy. With the release of the U.S. Marine Corps' Force Design 2030, this volume gives historians, theorists, and practitioners an opportunity to ground the coming changes in the historical context as they seek to find out what it takes to win on contested shores.